2019
DOI: 10.1186/s13063-019-3622-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different amounts of vitamin D supplementation on serum calcidiol, anthropometric status, and body composition in overweight or obese nursing women: a study protocol for a randomized placebo-controlled clinical trial

Abstract: Background The optimal vitamin D intake for nursing mothers with overweight or obesity has not been defined. Vitamin D concentrations are associated with body composition indices, particularly body fat mass. Few studies have investigated the relationship between hypovitaminosis D, obesity, anthropometric status, and body composition in nursing women. Thus, the present study aims to investigate whether vitamin D supplementation during lactation will improve vitamin D status, reduce body fat mass, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Combining the opinions of two investigators, the RevMan software was used for risk assessment. In addition, subgroup analysis was conducted according to BMI [overweight defined as 23–24.9, obesity as 25 or over 25 in Indian studies ( 21 ); overweight defined as 25–29.9, obesity as 30 or over 30 in other studies ( 22 )], region (Northern Europe and Asia), vitamin D supplement dose (relatively low dose, relatively medium dose, and relatively high dose; according to included studies, we have found that doses of included studies were 2,857 IU/day, 3,571 IU/day, and 8,571 IU/day, therefore, we defined 2,857 IU/day as relatively low dose, 3,571 IU/day as relatively medium dose, and 8,571 IU/day as a relatively high dose in this meta-analysis), intervention time [short term defined as <365 days and long term defined as ≥365 days according to some articles ( 6 , 23 29 )], sex (only female or and male), and criteria for prediabetes definition (according to IDF/WHO or ADA criteria).…”
Section: Methodsmentioning
confidence: 99%
“…Combining the opinions of two investigators, the RevMan software was used for risk assessment. In addition, subgroup analysis was conducted according to BMI [overweight defined as 23–24.9, obesity as 25 or over 25 in Indian studies ( 21 ); overweight defined as 25–29.9, obesity as 30 or over 30 in other studies ( 22 )], region (Northern Europe and Asia), vitamin D supplement dose (relatively low dose, relatively medium dose, and relatively high dose; according to included studies, we have found that doses of included studies were 2,857 IU/day, 3,571 IU/day, and 8,571 IU/day, therefore, we defined 2,857 IU/day as relatively low dose, 3,571 IU/day as relatively medium dose, and 8,571 IU/day as a relatively high dose in this meta-analysis), intervention time [short term defined as <365 days and long term defined as ≥365 days according to some articles ( 6 , 23 29 )], sex (only female or and male), and criteria for prediabetes definition (according to IDF/WHO or ADA criteria).…”
Section: Methodsmentioning
confidence: 99%
“…In a randomized controlled study, vitamin D supplement for obese and overweight ladies with vitamin D deficiency enhanced their anthropometric data. 10 The pathophysiology of obesity is not well understood. However, it has been determined that multiple genetic and environmental factors are involved.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown that vitamin D has a role in the metabolism of carbohydrates [36] and fats [37][38][39]. Several mechanisms have been proposed for this process.…”
Section: Discussionmentioning
confidence: 99%